A single mutation attenuates both the transcription termination and RNA-dependent RNA polymerase activity of T7 RNA polymerase. (15th October 2021) - Wu, Hui; Wei, Ting; Yu, Bingbing; Cheng, Rui; Huang, Fengtao; Lu, Xuelin; Yan, Yan; Wang, Xionglue; Liu, Chenli; Zhu, Bin
ABSTRACT: Transcription termination is one of the least understood processes of gene expression. As the prototype model for transcription studies, the single-subunit T7 RNA polymerase (RNAP) is known to respond to two types of termination signals, but the mechanism underlying such termination, especially the specific elements of the polymerase involved, is still unclear, due to a lack of knowledge with respect to the structure of the termination complex. Here we applied phage-assisted continuous evolution to obtain variants of T7 RNAP that can bypass the typical class I T7 terminator with stem-loop structure. Through in vivo selection and in vitro characterization, we discovered a single mutation (S43Y) that significantly decreased the termination efficiency of T7 RNAP at all transcription terminators tested. Coincidently, the S43Y mutation almost eliminates the RNA-dependent RNAP (RdRp) activity of T7 RNAP without impeding the major DNA-dependent RNAP (DdRp) activity of the enzyme. S43 is located in a hinge region and regulates the transformation between transcription initiation and elongation of T7 RNAP. Steady-state kinetics analysis and an RNA binding assay indicate that the S43Y mutation increases the transcription efficiency while weakening RNA binding of the enzyme. As an enzymatic reagent for in vitro transcription, the T7 RNAP S43Y mutant reduces the undesired termination in run-off RNA synthesis and produces RNA with higher terminal homogeneity.